Impact of value accounting, cost accounting, and mortgages on the financial crisis - Hashim, Hasan Talib; Mohammed Adhab Jasim, Abbas Ali Jumaah, (Opción, 2020)
The study aims to investigate the impact of value accounting, cost accounting, and mortgages on the financial crisis via descriptive and deductive approaches. The result of this study shows that all three variables have a significant and positive relationship with each other; these variables are further tested to confirm the results achieved by the Person correlation matrix. In conclusion, if the alternative is used to provide credible information to the regulators, it should work to provide both credible future obligations and the resources that are required to fulfill those obligations.